Boys of the Cloth: The Accidental Role of Church Reforms in Causing and Curbing Abuse by Priests - Miles, Vincent J. (Hamilton Books, 2012)
Drawing on the author’s unusual background as a seminarian turned scientist and business executive, Boys of the Cloth presents a unique analysis of the sexual abuse crisis in the Catholic Church. The book combines a first-hand account of seminary life during the 1960s—a period that turns out to be crucial for understanding the crisis—with explorations of the history of the seminary system, current scientific knowledge about abusive behavior, and the Church’s own investigations into the “epidemic” of abuse by its priests. Through the interplay between these topics, two paradoxical conclusions emerge. First, that the epidemic was caused by an ancient reform intended to eradicate rather than encourage clerical corruption. Second, that it was reversed by modern Church policies with no obvious connection to sexual abuse. Boys of the Cloth will transform your understanding of predatory behavior by priests and of measures that will be crucial to prevent it.